Developing Echo-Aware Teachers in Indian Teaching Programmes: Cultivating Reflective Practice for Enhanced Learning - Ranjan, Rajeev (Journal of Advanced Research in English & Education; Vol 10 No 2 (2025): Journal of Advanced Research in English and Education, 2025)
This article explores the critical need for integrating “echo-awareness” into Indian teacher education programmes. Echo-awareness, in this context, refers to a teacher’s capacity to deeply listen to and understand the diverse voices, experiences, and perspectives of their students and to allow these echoes to inform and shape their pedagogical practices. In the diverse and multilingual classrooms of India, cultivating this awareness is paramount for creating inclusive, equitable, and effective learning environments. The article argues that traditional teacher training often focuses on content delivery and standardised methodologies, neglecting the crucial element of reflective practice rooted in student feedback and classroom dynamics. This paper outlines ten key areas that need to be addressed within Indian teaching programmes to foster eco-aware teachers. These areas include developing active listening skills, understanding cultural and linguistic diversity, promoting empathy and emotional intelligence, utilising formative assessment for feedback, encouraging collaborative reflection, integrating technology for student voice, fostering critical self-awareness, implementing mentorship and peer observation, restructuring curriculum for student-centred learning, and advocating for policy changes that prioritise reflective practice. By addressing these aspects, Indian teacher education can move towards producing educators who are not only knowledgeable but also deeply attuned to the needs and experiences of their students, ultimately leading to improved learning outcomes and a more just and equitable education system.